علاقة بعض المتغيرات البايوميكانيكية بعدد من الاختبارات بيرك (BBS) لدى الأطفال المصابين بالشلل الدماغي النصفي بأعمار(8-12) سنة - قادر, أ.د.نهاد أيوب; ميديا, أ.م.د.شوان قادر; حمد, م.أواره صابر (Sulaimani Journal for Humanities, 2023)
The research aims: 1- Identifying the values of some biomechanical variables for paraplegic children aged (8-12) years. 2- To identify the relationship between some biomechanical variables and a number of Berg balance tests for paraplegic children aged (8-12) years. 3- Identifying the relationship between some biomechanical variables between them for a number of Berg balance tests for paraplegic children aged (8-12) years. The researchers used the descriptive approach in the manner of correlations to suit the nature of the problem, and the research sample included children with hemiplegic cerebral palsy at the Helena Center in Erbil Governorate, and four Berg balance tests were used to find the relationship with some of the biomechanical variables, and the researcher processed the data statistically using the statistical bag (SPSS) version (25). The researchers reached a number of conclusions, including: 1- There is no correlation between the biomechanical variables (knee angle, hip angle, knee angle at maximum flexion, angle at hip maximum flexion, time of movement, height of the center of body mass) and (Berg's balance test) for the test (sitting to standing) in children with cerebral palsy. two halves. 2- There is an inverse significant correlation between (right leg time) and (right leg angular velocity), as the time decreases, the angular velocity increases for this type of Berg test (put the substitute foot on the step while standing). 3- There is a significant correlation between (distance between the feet) and (Berg's balance test) (360-degree rotation), as the decrease in the distance between the feet decreases balance during the performance of the (360-degree rotation) test.
Keywords: hemiplegia cerebral palsy; Berg; biomechanical variables